Internet-based Technologies are the Tools for Promoting Sportsmanship in Pakistan - Burki, Maheen Hashim Khan; Toor, Shazia Ismail; Momineen, Farrah Ul; Kousar, Tehmina (Pakistan Journal of Humanities and Social Sciences, 2023)
In today's digital era, the sports industry is going through a remarkable transformation. It's no longer just a game; the integration of technology in sport is reshaping how teams operate, athletes train themselves, and fans like to engage. Various tools, platforms, and applications for online coaching, performance assessment, smart apparel, and footwear have been created. Thus, it can be inferred that a network of well-organized devices and sensors has emerged to revolutionize sports industry as a whole. However, in Pakistan, technological adoption is often neglected and prejudiced. In the context of sports, Pakistan exhibits a restricted range of diverse athletic activities, mostly adhering to traditional practices and displaying little integration of technology advancements. The primary objective of this research is to examine the impact of internet technology on the promotion of sportsmanship within the context of Pakistan. The researchers have conducted in-depth interviews with athletes and sports professionals, using theme analysis to transcribe and evaluate the participants' comments in a comprehensive manner. The results indicate that technology plays a crucial role in upholding the integrity of the game, and the incorporation of technology in sports may enhance Pakistan's overall performance index.